Baitulmal: Its Role as an Heir According to Fuqaha’ and Legal Practices in Malaysia - Abd Wahab, Nor Azlina; Muda, Mohd Zamro; Mohamed Said, Noor Lizza (Kajian Malaysia, 2026)
Baitulmal is a crucial institution with a significant role in preserving and managing the wealth of the Muslim community. During the early Islamic era, among the sources of baitulmal were inherited properties that were not exhausted by the heirs from among the ashāb furūd and inheritance that had no eligible heirs. According to Imam Shāfi‘ī and Imam Mālik, such inheritance must be entrusted to the baitulmal. However, after the fourth century of the Hijrah, later scholars of the Shāfi‘ī school, such as Imam al-Nawawī, stipulated that for the baitulmal to qualify as an inheritor, it must be well-managed and properly administered. In general, the states of Malaysia adhere to the original stance of the Shāfi‘ī school, which allocates surplus inheritance to the baitulmal. Hence, this study aims to examine the perspectives of Islamic jurists regarding the inheritance rights of the baitulmal and its position as an heir within the legal framework of Malaysia. This study employs a qualitative methodology, encompassing data collection through content analysis and interviews with informants, specifically selected baitulmal officers directly involved in the management of inheritance. The collected data is then analysed inductively to synthesise the research objectives. The findings of the study indicate that in Malaysia, the baitulmal is recognised as the party entitled to receive the surplus of a deceased person’s estate and serves as a trustee responsible for safeguarding Muslims’ property, including inherited assets. Nevertheless, various constraints must be addressed to ensure the smooth administration of baitulmal estates, thereby preserving the maṣlaḥah (benefit) of the Muslim community. In addition, it is essential to ensure that the assets under its management achieve the predetermined objectives, namely for the purposes of welfare and the socioeconomic development of the Muslim community in line with the provisions of shariah and the law.